Pula! a ene: occupying land in restituted Barolong homelands ‘rain! let it rain' - Bantsheng, Lesego (School of Architecture, Planning and Geomatics, 2026)
This project requires it to be presented as a story. A story of the Barolong Boo Rra Tshidi clan of the Tswana tribe who have settled in Makgobistad. Makgobistad is a large village situated in the northern part of the Northwest province, right at the Botswana border. Such permanent settlement is new to the Barolong. The image in the right indicates that merely 40years ago, the Barolong had been living in Traditional settlements! These traditional settlements were conceptualized by an intentional mission towards a plural cosmology (Maqsud et al 1991). This project is an enquiry into the hybridization of rural settlements from communal living – communal awareness of societal effects on the landscape – to individualism. Individualism introduced by various global factors such as education, spatial boundaries and compartmentalisation of belief systems (ibid). The enquiry begins in a Tswana settlement, Makgobistad, which is used to uncover and discover cosmology through mapping, literature and Indigenous Knowledge systems. These are used with the goal of understanding how the Barolong hybridized themselves into this global context. The project sets to understand the effects of permanent settlement on the cosmology of the Barolong and vice versa. As population numbers increase, the aim of this project is to inform settlement making in the face of Land Restitution and Climate Change. The enquiry becomes a question of how we settle as opposed to where.